Development of Geomath Media in Integrative Geometry Learning - Dhujjah, Nurul Ilmi Badrud (International Journal of Trends in Mathematics Education Research, 2024)
Learning media acts as a tool, stimulus, or trigger in conveying learning messages by teachers. The role of learning media for students is to help them understand the material easily, effectively, and efficiently. This research aims to: 1) Understand the development process and 2) Validate GeoMath learning media experts. This research is a type of research and development Research and Development (RnD). The research format uses before and after observations to find out student learning outcomes more comprehensively. The research subjects were 52 students of Class VIII MTsN 2 Malang City.The research results show that the GeoMath media development process uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) research procedure which ensures that each stage from needs analysis to final evaluation is carried out systematically and structured. Apart from that, overall the GeoMath application is suitable and valid for use as a learning support instrument. Validation for three aspects of learning media, namely media size, media skin design, and media content design, was considered quite good by the validator. Validation for three aspects of learning material, namely content quality, accuracy of coverage, and language, was assessed as very good by the validator. Validation for the integration aspect was assessed as very good and almost perfect by the validator. Validation for three practical aspects or usefulness of learning media, namely media quality, media appearance, and media content design, was assessed as very good and close to perfect by the validator.